Upaya Peningkatan Penjualan Batik New Colet Jombang Melalui Pemanfaatan Media Sosial Instagram: - Yuanita Soewarno; Ety Dwi Susanti (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The development of information and communication technology has changed the way individuals interact with others. The internet becomes a new digital space that creates a cultural space. It is unavoidable that the existence of the internet provides many conveniences to its users. Various access to information and entertainment from all over the world can be searched via the internet. The internet penetrates the boundaries of the dimensions of the user's life, time and space, which can be accessed by anyone, anytime and anywhere. This is the background of the change from conventional communication to modern and all-digital. Promotions carried out by companies have also undergone many shifts, many companies have switched from promotions through print or electronic media to social media promotions. In this study, researchers used the Jombang New Colet Batik as the object of research. This research is intended to find out and identify efforts to increase sales of Batik New Colet through the use of Instagram social media. In this study researchers used qualitative research methods. In this study, data collection techniques were carried out in natural settings (natural conditions), primary data sources, and data collection techniques were mostly participant observation and interviews. Which informants in this study are the owners, employees, and consumers of Batik Colet Jombang. The informants in this study were the owners, employees and consumers of Batik Colet Jomban. The informants in this study were the owners, employees and consumers of Batik Colet Jombang. Data analysis techniques are carried out interactively and continuously until complete so that the data is saturated. The data analysis technique of this study uses data reduction techniques, data presentation (data display), and conclusion drawing (verification). To check the validity of the data in this study, researchers used technique triangulation and source triangulation. The results of the study state that marketing via Instagram is an effective way of digital marketing. Instagram is the social media with the most users. Attractive photo displays, discount offers, good service, and quality goods will attract buyers. Sales of Batik new colet products are able to make people aware of the products of Batik new colet, marketing carried out by Batik new colet through Instagram is an effective and efficient way to increase sales, the process is not that long and does not require large enough capital, the promotions carried out are also sufficient. easy. From the results of interviews conducted by researchers, the various built-in Instagram features that are most frequently used are the hash tag and instastory features. Because business actors consider that these three features provide a considerable influence in increase sales. Keywords: Marketing, Social Media Marketing, Instagram